(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Computer System Validation (CSV) plays a critical role in ensuring regulatory compliance, data integrity, and operational efficiency within healthcare and life sciences organizations. This study evaluates workflow optimization, risk management integration, training effectiveness, and continuous improvement practices in CSV using a quantitative, survey-based research design. Data were collected from 480 professionals involved in validation, quality assurance, compliance, and information technology functions. Descriptive statistics, correlation analysis, regression modeling, and factor analysis were employed to assess relationships among key validation practices and compliance outcomes. Results indicate that while organizations are actively working to reduce redundant CSV steps, only a moderate level of workflow optimization has been achieved, highlighting opportunities for further efficiency improvement. Regression analysis confirms that workflow optimization and documentation streamlining significantly influence validation efficiency, explaining 38.5% of the variance in faster validation outcomes.Training and educational initiatives exhibit a very strong impact on regulatory adherence, accounting for 79.2% of the variance, emphasizing the critical role of competency-driven learning. Factor analysis further identifies a unified and dominant continuous improvement framework, explaining 77.53% of total variance, underscoring the importance of feedback mechanisms, innovation, leadership support, and adaptability to evolving technologies and regulations. Overall, the findings demonstrate that strategic workflow redesign, integrated risk management, targeted training programs, and structured continuous improvement frameworks are essential for enhancing CSV efficiency and compliance in healthcare organizations.